Insights into naphthalene degradation in aqueous solution and soil slurry medium: Performance and mechanisms. (March 2022) - Zeng, Guilu; Yang, Rumin; Zhou, Zhengyuan; Huang, Jingyao; Danish, Muhammad; Lyu, Shuguang
Abstract: The performance of naphthalene (NAP) degradation in peroxodisulfate (PDS) and peroxymonosulfate (PMS) oxidation systems by nano zero valent iron (nZVI) combined with citric acid (CA) activation was reported in aqueous solution and soil slurry medium. The results in aqueous solution tests indicated that 98.1% and 98.9% of NAP were individually degraded in PDS/nZVI/CA and PMS/nZVI/CA systems within 2 h when the dosages of PDS, PMS, nZVI and CA were 1.0 mM, 0.1 mM, 0.2 mM and 0.1 mM, respectively. The consequences of scavenging tests and electron paramagnetic resonance detection demonstrated that HO and SO4 − were the key factors on NAP removal. The presence of surfactants could consume ROSs and inhibit NAP removal. In addition, GC-MS was applied for the determination of NAP degradation intermediates, and three possible NAP degradation pathways were proposed in PDS oxidation process and two pathways in PMS oxidation process, respectively. The results in soil slurry medium showed that the presence of CA could promote the dissolution of soil minerals and the desorption of NAP from soil medium. 93.5% and 96.8% degradation of NAP were obtained in PDS/nZVI/CA and PMS/nZVI/CA systems within 24 h. Besides, the existence of DOM in soil could promote Fe(II)/Fe(III) cycle and NAP degradation through electron transfer. Based on the NAP degradation performance in the actual groundwater and soil medium, the above findings could provide basis and strong support for the potential application of PDS/nZVI/CA and PMS/nZVI/CA systems in the remediation of NAP contaminated sites. Graphical abstract: Image 1 Highlights: NAP degradation in actual groundwater and soil slurry medium was investigated. HO. and SO4 − were the key factors in PDS and PMS oxidation systems. The possible degradation pathways of NAP were proposed. The enhancement of citric acid for NAP removal was illuminated. The mechanism of NAP degradation influenced by DOM in soil was clarified.